Bilateral simultaneous non-arteritic anterior ischemic optic neuropathy with occlusion of unilateral cilioretinal artery: A case report - Utku Limon; Betül İlkay Sezgin Akçay; Erdem Akçay (İstanbul Kuzey Klinikleri, 2019)
A 45-year-old female patient consulted our hospital for bilateral visual loss. She was receiving hemodialysis for 15 years. At presentation ophthalmologic examination, her visual acuity was hand movements in the right eye and light perception negative in the left eye. The direct light response was weak in the right eye and absent in the left eye. A total afferent pupillary defect was detected in the left eye. Fundoscopy revealed bilateral sectorial pale, sectorial hyperaemia and swollen optic discs. On the left papilla, there were splinter haemorrhages. At the right eye, there was pale edema at superior maculo-papillary bunch that coherent with occlusion of the cilioretinal artery. She was diagnosed as non-arteritic ischemic optic neuropathy based on the clinical and funduscopic examination. Methylprednisolone intravenous 1000mg/day for three days, then, oral methylprednisolone 1 mg/kg/day were administered for one week. Simultaneous acetylsalicylic acid 325 mg/day and hydration with 0.9% 1000cc isotonic solution treatment started. After two months, visual acuities did not change in both eyes, and both optic disks were pale.